Editorial Vol. 3 - Ciarlini, Angelo; Azevedo, Leonardo; Barros, Márcio (Histórico da iSys - Brazilian Journal of Information Systems (SERVIDOR ANTIGO - UNIRIO), 2010)
Editorial da terceira edição da iSys